Laien, Wissen, Sprache Theoretische, methodische und domänenspezifische Perspektiven - Hoffmeister, Toke; Hundt, Markus; Naths, Saskia (Sprache und Wissen (SuW), 2021)
Research from various corners has already shone light on the issue of what speakers know about their own language and their attitudes towards it. However, a joint theoretical and empirical basis is still missing. This volume provides an overview of the latest research in the field of lay linguistics and collects contributions that provide new theoretical stimuli, innovative methodological approaches and practical research.